Targeting inflammation in diabetes: Newer therapeutic options - Agrawal, Neeraj Kumar (Baishideng Publishing Group Inc, 2014)
Inflammation has been recognised to both decrease beta cell insulin secretion and increase insulin resistance. Circulating cytokines can affect beta cell function directly leading to secretory dysfunction and increased apoptosis. These cytokines can also indirectly affect beta cell function by increasing adipocyte inflammation.The resulting glucotoxicity and lipotoxicity further enhance the inflammatory process resulting in a vicious cycle. Weight reduction and drugs such as metformin have been shown to decrease the levels of C-Reactive Protein by 31% and 13%, respectively. Pioglitazone, insulin and statins have anti-inflammatory effects. Interleukin 1 and tumor necrosis factor-α antagonists are in trials and NSAIDs such as salsalate have shown an improvement in insulin sensitivity. Inhibition of 12-lipo-oxygenase, histone de-acetylases, and activation of sirtuin-1 are upcoming molecular targets to reduce inflammation. These therapies have also been shown to decrease the conversion of pre-diabetes state to diabetes. Drugs like glicazide, troglitazone, N-acetylcysteine and selective COX-2 inhibitors have shown benefit in diabetic neuropathy by decreasing inflammatory markers. Retinopathy drugs are used to target vascular endothelial growth factor, angiopoietin-2, various proteinases and chemokines. Drugs targeting the proteinases and various chemokines are pentoxifylline, inhibitors of nuclear factor-kappa B and mammalian target of rapamycin and are in clinical trials for diabetic nephropathy. Commonly used drugs such as insulin, metformin, peroxisome proliferator-activated receptors, glucagon like peptide-1 agonists and dipeptidyl peptidase-4 inhibitors also decrease inflammation. Anti-inflammatory therapies represent a potential approach for the therapy of diabetes and its complications.